2014
DOI: 10.12659/ajcr.890318
|View full text |Cite
|
Sign up to set email alerts
|

Novel Development of Remitting Seronegative Symmetrical Synovitis with Pitting Edema (RS3PE) Syndrome due to Insulin Therapy

Abstract: Patient: Male, 67Final Diagnosis: Remitting seronegative symmetrical synovitis with pitting edema (RS3PE) syndromeSymptoms: Bilateral wrist swellingMedication: —Clinical Procedure: —Specialty: RheumatologyObjective:Unusual or unexpected effect of treatmentBackground:Remitting seronegative symmetrical synovitis with pitting edema (RS3PE) syndrome is a rare clinical entity characterized by the sudden onset of inflammatory arthritis and marked pitting edema on upper and lower extremities. RS3PE is considered a rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…2 The drugs reported in relation with RS3PE are insulin, DPP-4 inhibitors, rifampicin and nivolimab. [4][5][6] In the present case the clinical presentation and disease course of RS3PE due to saxagliptin showed a course similar to those related to the other etiologies but with the onset of disease at young age. Yamauchi et al reported two diabetic patients who developed RS3PE while taking DPP-4 inhibitors.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…2 The drugs reported in relation with RS3PE are insulin, DPP-4 inhibitors, rifampicin and nivolimab. [4][5][6] In the present case the clinical presentation and disease course of RS3PE due to saxagliptin showed a course similar to those related to the other etiologies but with the onset of disease at young age. Yamauchi et al reported two diabetic patients who developed RS3PE while taking DPP-4 inhibitors.…”
Section: Discussionsupporting
confidence: 68%
“…Most cases of RS3PE syndrome are idiopathic, although the syndrome has been associated with malignancy, rheumatologic diseases and some drugs. [2][3][4][5][6] In a meta-analysis evaluating 331 cases of RS3PE, it was shown that the relation of RS3PE with malignancy and rheumatologic diseases were 16.31% and 6.65% respectively. 2 The drugs reported in relation with RS3PE are insulin, DPP-4 inhibitors, rifampicin and nivolimab.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations